PRINCIPAL LEADERSHIP AND TEACHER PERFORMANCE IN PRIMARY EDUCATION: A BIBLIOMETRIC ANALYSIS AND SYSTEMATIC LITERATURE REVIEW - Eka Ulfiani; Sholeh Hidayat; Ujang Jamaludin (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to map the evolution of research trends and integrate empirical evidence about the relationship between principal leadership and teacher performance.Methodology – This study used bibliometric analysis and a systematic literature review (SLR). Bibliometric data were retrieved from Google Scholar using Publish or Perish, then analyzed with VOSviewer for keyword co-occurrence, citation networks, and thematic clusters. The SLR followed PRISMA procedures to identify and synthesize relevant journal articles. Inclusion criteria required articles to be (1) published in peer-reviewed journals; (2) focus on principal leadership and teacher performance as main variables; and (3) address primary education.Findings – The findings show that (1) research on principal leadership and teacher performance has increased significantly in recent years. Dominant themes include performance, motivation, trust, and professional development. (2) Transformational, visionary, and instructional leadership are the most frequently examined models. (3) Principal leadership influences teacher performance mainly through mediating factors such as organizational commitment, job satisfaction, and professional learning. In conclusion, principal leadership plays a strategic and multidimensional role in enhancing teacher performance. An integrative perspective is essential to strengthen future research and policy development.Contribution – This study offers an integrative, multi-layered framework. The framework connects bibliometric trends with empirical synthesis. It clarifies how various principal leadership models systematically shape teacher performance in primary education through psychological, professional, and organizational pathways.